Lecturer Attitudes and Behavioural Intentions to Use Learning Management Systems in Vietnam - Pham Ngoc Thach; Phuong Hoai Lai (Flexible Learning Association of New Zealand, 2022)
This study aims to explore lecturer attitudes to, and intentions for, using a learning management system (LMS) in a Vietnamese university. Its two main purposes are to (a) identify the factors that influence lecturer attitudes and intentions to use an LMS, and (b) examine the causal relationships among the factors. To achieve this aim, the study used Davis' (1985) technology acceptance model (TAM) as a baseline. The study expands the original model to include two constructs: perceived internet self-efficacy (PIS), and support to use (SU). The results of the study revealed that PIS was a significant direct predictor of lecturers' perceived ease of use and behavioural intention to use an LMS. However, the support to use construct did not predict perceived ease of use. The study suggests that institutions should conduct an in-depth survey of teacher needs to assist with making well-informed decisions about developing an LMS for future emergencies.